Nonlinear dynamics of the coupled exciton-cavity system - Meier, Torsten; Koch, M.; Shah, J. (Quantum Electronics and Laser Science Conference)
In recent years the linear emission dynamics of microcavities containing an optical absorber has been a subject of intense research. For strong coupling between the cavity and the absorber, the spectrum of the coupled system shows two peaks and the linear dynamics of the coupled system is dominated by pronounced oscillations at the normal mode frequency.1 Yet, the uniqueness of the coupled absorber-cavity system cannot be concluded from its linear dynamics.

Multiple Exciton Coherence Sizes in Photosynthetic Antenna Complexes viewed by Pump-Probe Spectroscopy - Meier, Torsten; Chernyak, V.; Mukamel, S. (The Journal of Physical Chemistry B)
The pump−probe signal from the light-harvesting antenna LH2 of purple bacteria is analyzed using a Green function expression derived by solving the nonlinear exciton-oscillator equations of motion (NEE). A microscopic definition of the exciton mean free path (Lf) and localization size (Lρ) is given in terms of the off-diagonal elements of the exciton Green function and density matrix, respectively. Using phonon-induced (homogeneous) and disorder-induced (inhomogeneous) line widths compatible with superradiane measurements, we find that at 4.2 K the localization size is Lρ = 15 and that the shift ΔΩ between the positive and negative peaks in the differential absorption is determined by a different effective size Lf/2 = 5.6 associated with the exciton mean free path. Our model further predicts the recently observed superradiance coherence size determined by Lρ.

(4×2) and (2×4) reconstructions of GaAs and InP(001) surfaces - Schmidt, Wolf Gero (Applied Physics A: Materials Science & Processing)

The anisotropic electron - positron momentum distribution in diamond - Nilen, R W N; Connell, S H; Britton, D T; Fischer, C G; Sendezera, E J; Schaaff, P; Schmidt, Wolf Gero; Sellschop, J P F; Verwoerd, W S (Journal of Physics: Condensed Matter)

Electron-positron momentum density distribution in diamond - Nilen, R.W.N.; Connell, S.H.; Schmidt, Wolf Gero; Britton, D.T.; Verwoerd, W.S.; Sellschop, J.P.F.; Shrivastava, S. (Applied Surface Science)

Antimony-stabilized GaAs(001)(2×4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Chemisorption of arsenic on InP(110) - Großner, U.; Schmidt, Wolf Gero; Bechstedt, F.; Santos, P.V.; Koopmans, B.; Esser, N. (Surface Science)

Comparison of As-rich and Sb-terminated GaAs(100)(2 × 4) reconstructions - Schmidt, Wolf Gero; Bechstedt, F. (Surface Science)

A High Resolution Investigation of the Anisotropic Electron-Positron Momentum Distribution in Diamond - Nilen, R.W.N.; Connell, S.H.; Britton, D.T.; Fischer, C.G.; Sendezera, E.J.; Schmidt, Wolf Gero; Sellschop, J.P.F.; Verwoerd, W.S. (Materials Science Forum)

As on InP(110) studied within density-functional theory - Grossner, U.; Schmidt, Wolf Gero; Bechstedt, F. (Physical Review B)

Coherent Dynamics of Semiconductor Heterostructures - Meier, Torsten; Koch, S.W.; Stroucken, T.; Knorr, A.; Hader, J.; Rossi, F.; Thomas, P. (Microscopic Theory Of Semiconductors: Quantum Kinetics, Confinement and Lasers)

Dephasing of interacting heavy-hole and light-hole excitons in GaAs quantum wells - Meier, Torsten; Bott, K.; Mayer, E.J.; Smith, G.O.; Heuckeroth, V.; Hübner, M.; Kuhl, J.; Schulze, A.; Lindberg, M.; Koch, S.W.; Thomas, P.; Hey, R.; et al. (Journal of the Optical Society of America B)
We describe a novel three-pulse degenerate four-wave mixing configuration that permits the direct observation of the coherence between the σ+ and the σ− exciton states in a GaAs quantum well excited in a two-photon process. It is found that the phase coherence between the two single heavy-hole exciton states decays with a time constant that is considerably longer than the dephasing time of the coherence between these states and the ground state (interband coherence). All the experimental data are well described by numerical solutions of the optical Bloch equations for a phenomenological multilevel model.

On the Observability of dynamic localization in semiconductor superlattices using optical spectroscopy - Meier, Torsten; Rossi, F.; Je, K.-C; Hader, J.; Thomas, P.; Koch, S.W. (Hot Carriers in Semiconductors)
During the last decade, a variety of field-induced coherent phenomena in semiconductor superlattices has received considerable attention both from a theoretical and from an experimental point of view. For the case of a static applied electric field, the existence of Bloch oscillations has been predicted theoretically and confirmed by means of different experimental techniques of nonlinear optical spectroscopy.

Microscopic theory of the Bloch-oscillation dynamics in semiconductor superlattices: Intra- versus interband Dephasing - Meier, Torsten; Rossi, F.; Gulia, M.; Selbmann, P.E.; Molinari, E.; Thomas, P.; Thomas, P.; Koch, S.W. (Proceedings of the 23rd ICPS)

Exciton ionization induced by an electric field in a strongly coupled GaAs/AlxGa1-xAs superlattice - Meier, Torsten; von Plessen, G.; Koch, M.; Feldmann, J.; Thomas, P.; Koch, S.W.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Physical Review-Section B-Condensed Matter)
We study exciton ionization induced by an axial electric field in a strongly coupled GaAs/Al0.3Ga0.7 As superlattice at low temperatures. The field-induced ionization times of the heavy-hole 1s exciton in the miniband field regime are determined from transient four-wave-mixing experiments and theoretical model calculations. They are found to decrease with increasing field, and lie in the picosecond and subpicosecond ranges for fields on the order of a few kV/cm. They are considerably longer than those calculated for a 1s exciton in bulk GaAs. We explain this difference as a result of the nonparabolicities in the superlattice miniband dispersion. In addition to studying the field-induced ionization of the 1s resonance, we also investigate the field dependence of excitonic wave packets composed of both bound and continuum states of the exciton. It is found that the continuum components of the wave packet are more sensitive to low electric fields than the 1s component. © 1996 The American Physical Society.

Disorder mediated biexcitonic beats in semiconductor quantum wells - Meier, Torsten; Albrecht, T.F.; Bott, K.; Schulze, A.; Koch, M.; Cundiff, S.T.; Feldmann, J.; Stolz, W.; Thomas, P.; Koch, S.W.; Göbel, E.O. (Physical Review B)
Beats in the transient four-wave-mixing signal from strongly inhomogeneously broadened semiconductor quantum wells are observed. Based on their phase and polarization properties, the beats are assigned to biexcitons in the mesoscopically disordered material. With increasing excitation intensity a halving of the beat period is observed and is accurately reproduced by calculations including fifth-order contributions.

Femtosecond Spectroscopic Signatures of Electronic Correlations in Conjugated Polyenes and Semiconductor Nanostructures - Meier, Torsten; Mukamel, S. (Physical review letters)
Electronic correlation effects which can be directly probed by ultrafast four-wave mixing are predicted using the electronic-oscillator representation of conjugated polyenes. Comparison with inorganic semiconductors is made possible since the semiconductor Bloch equations projected onto the lowest exciton are obtained as a limiting case. A sign difference in a nonlinear scattering potential clearly shows up in the Wigner spectrogram representing the time and frequency resolved signal.

Field-induced exciton ionization studied by four-wave mixing - Meier, Torsten; Koch, M.; von Plessen, G.; Feldmann, J.; Koch, S.W.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Kuo, J.M.; Kopf, R.F. (Hot Carriers in Semiconductors)
The dynamics of carriers induced by electric fields in semiconductor superlattices has received much interest in recent years. Phenomena like Bloch oscillations and negative differential velocity in these structures have been studied using a variety of experimental techniques [1–5]. One particular point of interest has been the transition of the miniband regime to the Bloch oscillation regime with increasing electric field [6,7]. Cw spectra of strongly-coupled superlattices have evidenced that this transition is concomitant with a rapid field-induced ionization of the zero-field miniband exciton [5,8]. While it has been pointed out from the theoretical side that the field-induced ionization process strongly influences the coherent dynamics in the transition region [9], no systematic experimental investigation of the ionization process has been carried out so far. One interesting question that such an investigation could help to answer is to what extent this ionization process differs from the well-documented case of field-induced exciton ionization in bulk semiconductors.

Equilibrium and nonequilibrium optical effetcs in semiconductor heterostructures - Meier, Torsten; Koch, S.W.; Hader, J.; Je, K.-C; Rossi, F.; Thomas, P. (Frontiers in Nanoscale Science of Micro/Submicro Devices)

Phonon-Induced Suppression of Bloch Oscillations in Semiconductor Superlattices: a Monte Carlo Investigation - Meier, Torsten; Rossi, F.; Thomas, P.; Koch, S.W.; Selbmann , P.E.; Molinari, E. (Hot Carriers in Semiconductors)
The progress in the generation of ultrashort laser pulses, together with the development of spectroscopies on this time-scale, has led to a series of experiments which give new insight into the microscopic carrier dynamics in semiconductors. In particular, the energy relaxation of photoexcited carriers has been widely investigated. At the same time, recent progress in the fabrication and characterization of semiconductor heterostructures and superlattices allows a detailed study of a new class of phenomena induced by an applied electric field, such as Bloch oscillations1,2. Both classes of phenomena typically occur on a pico- or femtosecond time-scale, where the coupling between coherent and incoherent phenomena is known to play a dominant role3. Therefore, an adequate theoretical model of the ultrafast dynamics on this time-scale must account for both coherent and incoherent effects on the same kinetic level.